Childhood maltreatment modifies the relationship of depression with hippocampal volume. Issue 16 (24th July 2015) - Gerritsen, L.; van Velzen, L.; Schmaal, L.; van der Graaf, Y.; van der Wee, N.; van Tol, M.-J.; Penninx, B.; Geerlings, M.
Abstract : Background: Childhood maltreatment (CM) may modify the relationship between major depressive disorder (MDD) and hippocampal volume reduction. To disentangle the impact of MDD and CM on hippocampal volume we investigated the association between MDD and hippocampal volume in persons with and without a history of CM in two independent cohorts. Method: We used data of 262 participants from the Netherlands Study of Depression and Anxiety (NESDA) (mean age 37 years, 32% male) and 636 participants from the SMART-Medea study (mean age 61 years, 81% male). In both studies a 12-month diagnosis of MDD and CM were assessed using a diagnostic interview. Hippocampal volume was measured in NESDA using FreeSurfer software on 3-T magnetic resonance (MR) images and in SMART it was manually outlined on 1.5-T MR images. With analysis of covariance adjusted for intracranial volume, age, gender and lifestyle factors we estimated the effects of MDD and CM on hippocampal volume. Results: In both cohorts CM was not significantly associated with hippocampal volume. After pooling the data MDD was associated with smaller hippocampal volume ( B = −138.90 mm 3, p = 0.05) and the interaction between MDD and CM reached significance ( p = 0.04); in participants with CM, MDD was related to smaller hippocampal volume (NESDA: B = −316.8 mm 3, p = 0.02; SMART: B = −407.6, p = 0.046), but not in participants without CM ( p > 0.05). Conclusions: Our study shows that in two independent cohorts, particularly in individuals with CM, a diagnosis of MDD is related to smaller hippocampal volume. Prospective studies are needed to further determine through which mechanism CM may amplify the relationship between MDD and hippocampal volume.